Influence of the π-coordinated arene on the anticancer activity of ruthenium(II) carbohydrate organometallic complexes - Hanif, Muhammad; Meier, Samuel; Nazarov, Alexey; Risse, Julie; Legin, Anton; Casini, Angela; Jakupec, Michael A.; Keppler, Bernhard K.; Hartinger, Christian G. (Frontiers in Chemistry, 2013)
The synthesis and in vitro cytotoxicity of a series of RuII(arene) complexes with carbohydrate-derived phosphite ligands and various arene co-ligands is described. The arene ligand has a strong influence on the in vitro anticancer activity of this series of compounds, which correlates fairly well with cellular accumulation. The most lipophilic compound bearing a biphenyl moiety and a cyclohexylidene-protected carbohydrate is the most cytotoxic with unprecedented IC50 values for the compound class in three human cancer cell lines. This compound shows reactivity to the DNA model nucleobase 9-ethylguanine, but does not alter the secondary structure of plasmid DNA indicating that other biological targets are responsible for its cytotoxic effect.